FAKTOR PENGARUH PADA KEPUTUSAN PEMBELIAN TIKET PESAWAT DI APLIKASI TRAVELOKA - Mustika Putri, Yulisvi; Ari Wibowo, Purnomo; Aji Samekto, Agus; Supriyanto, Supriyanto; Ngaijan, Ngaijan; Mawardi, Kholid (Populer: Jurnal Penelitian Mahasiswa, 2022)
The purpose of this study was to determine whether or not the influence of customer experience, consumer confidence, prices and flight ticket purchasing decisions on the Traveloka application for UNIMAR AMNI Semarang Students. The sample in this study amounted to 52 respondents who used airline ticket services in the Traveloka application. By using probability sampling technique, namely by random sampling. Analysis of the data used in this study is descriptive analysis and quantitative analysis, the data were analyzed using multiple linear regression analysis with the help of (software) Statistical Package For Social Science (SPSS) version 26. The results of the study by partially testing the t-test hypothesis showed that Customer experience, consumer trust, and price have a positive and significant effect on purchasing decisions. Based on the research results, it can be seen that the research model of the multiple linear regression equation is Y= 0.095 + 0.484.X1 + 0.195.X2 +0.295.X3 + . From the regression equation, it can be seen that the most dominant variable affecting the increase in the number of passengers is the price variable with a regression coefficient of 0.095. And the R2 test (Adjusted R Square) obtained results of 0.780 or 78.0% which means that purchasing decisions are influenced by customer experience, consumer confidence and price variables which are 63.8% and other factors that influence passenger decisions are 36.2 % or 0.362.